Alternative alamat myths and legends from the Philippines an anthology - Chikiamco, Paolo; Malonzo, Mervin (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2022)
"Alamat are legends passed down, tales that often reflect the unique blend of fantasy and folklore that has so deeply influenced Filipino life and culture. Representing a range of exciting voices in speculative fiction, this essential anthology offers richly reimagined realms where mythic heroes, powerful gods and fantastic creatures vie for influence in human lives. Fusing folklore, myth and magic, Alternative Alamat reinvents and reimagines Philippine mythology for a new generation of fantasy fiction lovers." --Book jacket.